2017
DOI: 10.1016/j.jped.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of contextual variables in the evaluation of child abuse in the pediatric emergency setting

Abstract: Patterns of association between victims, family contexts, and abusers were identified. It is necessary to alert clinicians about the importance of social variables in the multiple facets of child abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…This study fits with others in which researchers have identified temporal variation in child abuse and neglect, including more cases in spring and summer 21,22 than in autumn and winter, 23 more physical abuse-associated visits to the hospital in the afternoon to evening hours, 22 and more physical abuse-associated hospital admissions during weekdays. 24 One study of children in China 25 found peaks in physical abuseassociated hospital admissions in the 2 months preceding school examination periods.…”
Section: Discussionsupporting
confidence: 90%
“…This study fits with others in which researchers have identified temporal variation in child abuse and neglect, including more cases in spring and summer 21,22 than in autumn and winter, 23 more physical abuse-associated visits to the hospital in the afternoon to evening hours, 22 and more physical abuse-associated hospital admissions during weekdays. 24 One study of children in China 25 found peaks in physical abuseassociated hospital admissions in the 2 months preceding school examination periods.…”
Section: Discussionsupporting
confidence: 90%